Incidental p16-positive oropharyngeal carcinoma found during tonsillectomy for palmoplantar pustulosis - Mitsuo P. Sato; Naoki Otsuki; Mutsukazu Kitano; Katsumi Doi (Acta Oto-Laryngologica Case Reports, 2021)
The tonsillar crypt is thought to be a hiding site for early cancer detected after tonsillectomy for primary lesion search in cancer of unknown primary site. In rare cases, a small lesion can be detected unexpectedly during surgical treatment for chronic tonsillitis and tonsillar focal diseases. We report the case of a 47-year-old woman undergoing tonsillectomy for palmoplantar pustulosis (PPP), resulting in the diagnosis of p16-positive oropharyngeal cancer (OPC) in the left tonsil. Postoperative radiation therapy was performed due to the presence of an adhesive lesion during surgery. Radiotherapeutic adverse effects were mild and improved 3 months after the radiotherapy. The symptoms of PPP completely resolved 3 months after the tonsillectomy and no recurrence has been observed so far. With an increase in the cases of HPV-related OPCs, routine pathological examination after tonsillectomy for benign-appearing tonsils in adults is necessary to detect incidental OPC regardless of its low cost-effectiveness.